Development of and access to banking services in Poland and Georgia - Nowacka, Anna; Szewczyk-Jarocka, Mariola; Kbiladze, Tamar; Dapkus, Rimantas (Transformations In Business & Economics, 2026)
The aim of the study is to determine the level of development of banking services in terms of access to banking service infrastructure in Poland and Georgia. Comparisons of the development of and access to banking service infrastructure were made with a set of indicators using the Mann-Whitney U and Kolmogorov-Smirnov tests and regression analysis. The development of and access to banking services in Poland and Georgia reveals both the similarities and differences. Undoubtedly, the common feature is the reduction of physical bank branches and the development of electronic banking infrastructure. Poland has a more developed POS network. Georgia, on the other hand, has a higher average number of cards per capita and a bigger network of ATMs.
Keywords: banking services; accessibility; development; banking service infrastructure; banking sector